Yoko Ono - Anderson, Laurie 1947-; Osaka, Eriko; Raspail, Thierry 1951- (Phaidon, 2024)
The definitive monograph on the work of celebrated visual artist, musician and peace activist Yoko Ono Born in Tokyo in 1933, Yoko Ono is one of the most important living artists working today. In a career that spans over six decades, Ono has experimented with a broad variety of media, including music, performance art, and film. Mostly known for her early involvement with the Fluxus art movement in the late 1950s and her professional and personal association with Beatles frontman John Lennon, Ono’s ground-breaking work has been influential to generations of artists as well as her incessant campaigning for World peace.
Keywords: Ono, Yōko -- 1933-; Paperback / softback; monograph; visual artist; musician; peace activist; Monografie; Bildende Künstlerin; Musikerin; Friedensaktivistin; Yoko Ono; 1583: Hardcover, Softcover / Kunst/Bildende Kunst; Bildband